LEGAL DEVELOPMENT BASED ON LOCAL WISDOM AS THE BASIS OF A SETTINGS FOR RELIGIOUS LIFE IN CENTRAL JAVA - Rini Fidiyani; Baidowi . (Jurnal Dinamika Hukum, 2015)
The constitution guarantees freedom of religious life in Indonesia. This guarantee is becoming a myth that is caused by the inability of the state or its agents in fulfilling the promises of its constitution. Religious life in Central Java that seems comfortable but it seems to keep fire. This study is a qualitative research with anthropology, ethnography and law approach. The results shows that the religious conflicts that occurred in Central Java, is because the inappropiate view of the religious exclusivism and the decreasing local wisdom in daily life. Though Central Java have local wisdom which can be used as material development of laws in conflict resolution. But there is a juridical obstacles in its development, because of the unsynchron between the law relating to local authorities in making policy of inter-religious conflict resolution. Therefore, the development of laws based on local wisdom can be done if the juridical obstacles is overcome first.Keywords: freedom of religion, local wisdom, exclusivism, inclusivism, juridical obstacles, social conflict.